Stock market reactions to monetary policy surprises under uncertainty - Jonathan Benchimol; Yossi Saadon; Nimrod Segev (International Review of Financial Analysis, 2023)
This article investigates how uncertainty impacts the effect of monetary policy surprises on stock returns. Using high-frequency US data, we demonstrate that stock markets respond more aggressively to monetary policy surprises during periods of high uncertainty. We also show that uncertainty asymmetrically influences the transmission of positive and negative monetary policy surprises to stock market prices. The amplifying effect of uncertainty is found to be stronger for expansionary shocks than for contractionary shocks. Our robustness analysis confirms that financial uncertainty has a significant role in shaping the influence of monetary policy on the stock market.
Keywords: E44; E52; E58; G12; G14; D53; 330; Monetary policy; Uncertainty; Stock returns; High-frequency data; Shock identification; Event study; Stock markets; Central bank communication; Volatility